2015
DOI: 10.1007/s12024-015-9679-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduced reaction volumes and increased Taq DNA polymerase concentration improve STR profiling outcomes from a real-world low template DNA source: telogen hairs

Abstract: Overall, this study highlights the importance and benefit of optimizing PCR conditions and developing improved laboratory methods to amplify and analyze LTDNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This result suggested that correct genotyping could be obtained when the PCR volume was reduced to 5 μl. In some forensic cases with trace or low levels of template DNA, the PCR reaction volume was often reduced to improve the reliability and sensitivity of STR profiling (Gibson‐Daw, Crenshaw, & McCord, 2018; McNevin, Edson, Robertson, & Austin, 2015). A lower PCR reaction volume would sometimes be chosen to deal with low copy DNA (Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This result suggested that correct genotyping could be obtained when the PCR volume was reduced to 5 μl. In some forensic cases with trace or low levels of template DNA, the PCR reaction volume was often reduced to improve the reliability and sensitivity of STR profiling (Gibson‐Daw, Crenshaw, & McCord, 2018; McNevin, Edson, Robertson, & Austin, 2015). A lower PCR reaction volume would sometimes be chosen to deal with low copy DNA (Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the incorporation of multiple TaqMan probes for signal generation did somewhat reduce overall PCR efficiency, necessitating the use of a higher number of cycles to reach the PCR plateau phase. However, we note that overall assay time could likely be reduced though optimization of the PCR reaction (e.g., increasing the concentration of DNA polymerase or utilizing a DNA polymerase with stronger exonuclease activity). While LiNC PCR can be performed using conventional TaqMan probes, incorporation of LNA sequences allows for the use of shorter, more specific probes, thereby increasing the possible number of probe sites in each LP as well as improving the performance of the method by enhancing the signal-to-noise ratio. , It is worth noting that the LiNC PCR method demonstrated here for broad-based detection of target sequences; it is in principle readily amenable and ideally suited for use with digital PCR (dPCR)-based methods , to unlock the full multiplexing potential of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification kits are generally not considered to be a significant factor in a profiles' dropout rate, however many studies have compared the performance of different STR kits and also at low DNA amounts [24,40,41], i.e., for a comprehensive investigation of STR amplification success for touch DNA applications [12]. Moreover, a plethora of studies [24,27,[42][43][44][45][46][47][48] indicate that the use of a reduced amplification volume increases PCR sensitivity. Tay et al [40] examined the performance of three forensic autosomal STR kits on buccal cells according to their manufacturers' recommendations (using DNA ranges from 0.008 to 2 ng).…”
Section: Dilution Studymentioning
confidence: 99%